Clinical researchLow-dose fentanyl: hemodynamic response to endotracheal intubation in normotensive patients - Channaiah, Vijayalakshmi B.; Chary, Kempa; Vlk, Jennifer L.; Wang, Yao; Chandra, Sathees B.C. (Archives of Medical Science, 2008)
Introduction: Endotracheal intubation is one of the most invasive stimuli in anesthesia, often accompanied by a hemodynamic pressor response. The purpose of this study was to investigate the efficacy of a single pre-induction 2 µg/kg bolus injection of fentanyl with a thiopentone/suxamethonium sequence in the attenuation of the hemodynamic response to endotracheal intubation in normotensive patients. Material and methods: The study consisted of 100 randomly selected ASA physical status I/II male/female adults, aged 18-60 years, scheduled for elective surgery. Group I received a single 2 µg/kg IV bolus of fentanyl diluted to 5 ml with normal saline 5 min prior to laryngoscopy (n=50). Group II received a single 5 ml IV bolus of normal saline (n=50). Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and rate pressure product (RPP) were compared to basal values at pre-induction, induction, intubation and post-intubation, at time increments of 1, 3, 5, 7 and 10 min. Results: Fentanyl significantly attenuated hemodynamic pressor responses. Attenuation of HR (10.9%), SBP (12.4%), DBP (9.4%), MAP (11.3%) and RPP (23.3%) were observed in the fentanyl group as compared to the equivalent control measured values. Conclusions: Single pre-induction 2 µg/kg bolus injection of fentanyl in a thiopentone/suxamethonium anesthetic sequence successfully attenuates, but does not suppress, the hemodynamic pressor response in normotensive patients resulting from endotracheal intubation.